The Oxidation Cascade of a Rare Multifunctional P450 Enzyme Involved in Asperterpenoid A Biosynthesis - Huang, Hui-Yun; Huang, Jia-Hua; Wang, Yong-Heng; Hu, Dan; Lu, Yong-Jun; She, Zhi-Gang; Chen, Guo-Dong; Yao, Xin-Sheng; Gao, Hao (Frontiers in Chemistry, 2021)
The cytochrome P450 enzymes (P450s or CYPs) are heme-containing enzymes which catalyze a wide range of oxidation reactions in nature. In our previous study, a rare multifunctional P450 AstB was found, which can dually oxidize two methyl groups (C-19 and C-21) of preasperterpenoid A to asperterpenoid A with 3-carboxyl and 11-hydroxymethyl groups. However, the oxidation order of C-19 and C-21 catalyzed by AstB is unclear. In order to reveal this oxidation order, probable pathways catalyzed by AstB were proposed, and the oxidation order of C-19 and C-21 was obtained by quantum chemistry calculations. The potential intermediates (three new asperterpenoids D–F, 1–3) were obtained through the chemical investigation on the extract of the transformant strain and chemical conversions, which were used as the standards to detect their existences in the extract of the transformant strain with HPLC-MS. Combined with the quantum chemistry calculation and the HPLC-MS analysis, the catalyzed order of AstB in asperterpenoid A biosynthesis was revealed. Furthermore, the mPTPB inhibition of obtained asperterpenoids was evaluated, and the results showed that 3-carboxyl and the oxidation station of C-21 would be the key factors for mPTPB inhibition of asperterpenoids.